Pengaruh dukungan sosial terhadap pola pengasuhan orang tua anak berusia middle childhood dari keluarga miskin - Evelyn, Evelyn; Savitri, Luh Surini Yulia (Jurnal Psikologi Ulayat: Indonesian Journal of Indigenous Psychology, 2015)
This study aimed to determine the effect of social support on parenting style of middle childhood parents from poor families. A total of 78 parents were involved in the study by completing questionnaires to measure social support and parenting style. Social support was measured by using Multidimensional Scale of Perceived Social Support from Zimet et al. (1988), whereas parenting styles were measured by using Parenting Style Development Questionnaire Short Version from Robinson et al. (1995). In this study, 74 participants were found to apply authoritative parenting style, two applied authoritarian parenting style, and two others applied permissive parenting style. The result of this study indicates that social support has no significant effect on both authoritative and permissive parenting style. In contrast, social support affects authoritarian parenting style significantly.